Spatial disorientation in right-hemisphere infarction. - Meerwaldt, J D (1982)
Spatial orientation was tested with the rod orientation test. The subjects were 40 normal controls and 68 brain-damaged patients with cerebral infarcts. Patients in whom the lesion included the post-rolandic region of the right hemisphere performed worse than controls or patients with lesions at other sites. Patients with an exclusively postrolandic (usually occipital) lesion showed higher error rates than patients with a combined prerolandic and postrolandic lesion, but only for the visual part of the test. These patients were re-examined one year after the stroke. Most of them showed an incomplete recovery of spatial function.